Evaluation of guar gum-based biopolymers as binders for lithium-ion batteries electrodes. (1st March 2018) - Carvalho, Diogo Vieira; Loeffler, Nicholas; Hekmatfar, Maral; Moretti, Arianna; Kim, Guk-Tae; Passerini, Stefano
Abstract: Herein we report the investigation on the use of guar gum and two of its derivatives as LIB positive electrodes binders. These polymers are electrochemically stable within the operating voltage of LIBs (0.01–5 V vs Li/Li + ) and do not show evidence of thermal decomposition up to 200 °C. The electrochemical performance of lithium nickel manganese cobalt oxide (NMC) electrodes made using guar gum is excellent as indicated, for instance, by the delivered capacity of 100 mAh g −1 upon 5C rate cycling. X-ray Photoelectron Spectroscopy (XPS) measurements of pristine electrodes reveal as the binder layer surrounding the active material particles is thin, resulting in the above-mentioned electrochemical performance. Full lithium-ion cells, utilizing guar gum on both positive and negative electrodes, display a stable discharge capacity of ∼110 mAh g −1 (based on cathode active material) with high coulombic efficiencies. Post-mortem investigation by XPS of cycled graphite electrodes from full lithium-ion cells revealed the formation of a thin solid electrolyte interface (SEI). Highlights: Guar gum as aqueous binder for LIB electrodes. Effect of guar gum on the SEI formed on graphite and NMC. Mechanical properties of guar gum-based electrodes.